(untitled) (Anclajes, 2018)
Argentine writer Tununa Mercado (Córdoba, 1939-) responds to several questions that enable opening new edges in contemporary literary criticism regarding gender and feminism. In this interview, she alludes to the composition of her works, her exiles, her militancy and her various jobs, including journalism and translation. She refers also to the link between memory and writing, teaching, the political, the autobiographical, the complexity of writing and what she lived as experience.